ANALISIS FENOMENA KEHIDUPAN SEORANG PEKERJA SEKS KOMERSIAL (PSK) YANG BERKELUARGA DI DESA SIDOMULYO KABUPATEN PROBOLINGGO - Fika Anjana; Maula Nasrifah (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
ABSTRACTThis study aims to analyze the phenomenon of a commercial sex worker (PSK) life who has a family in the village of Sidomulyo, Probolinggo Regency. Interpretative is used to determine the paradigm of this research. Emile Durkheim's Social Fact Theory has a major role in conducting this research. While the method used in this research is qualitative. Interviews, observation, and documentation are the methods used in this study to retrieve data.The results of this study explain that: First, the Social Interaction, Social Contact, and Social Communication of PSK with the community is going well, there has never been any conflict or dispute, this is in accordance with the Social Interactions that occur between PSK and the surrounding community. Second, the communication relationship between PSK and the community is going well, because among them there is a sense of mutual respect, mutual respect, and mutual help between each other and besides that, PSKalso feel comfortable living in the village, because it has become a familiar place for the PSK. Third, PSK considers that the surrounding community is their own family, this proves that the form of sympathy possessed by sex workers is very high for the surrounding community. Fourth, the Social Interaction between PSK went well, it was proven by the absence of conflict, dispute, contradiction, and competition.Keywords: the phenomenon of a commercial sex worker (PSK) life who has a family